Model Kelembagaan Terpadu Pencegahan Kebakaran Hutan Dan Lahan Di Kabupaten Kepuluan Meranti Provinsi Riau - Jufri Jufri; Sujianto Sujianto; Bintal Amin; Efriyeldi Efriyeldi (Universitas Riau, 2018)
Riau is one of the most vulnerable provinces to forest and land fires in Indonesia, Meranti Islands Regency Riau Province is one of the worst places. Forest and land fires in the Meranti Islands Regency occur during the dry season. Various prevention efforts have been carried out by the government. Meranti Islands Regency 60% is this peat area which causes opportunities for forest and land fires. This study analyzes: 1) the causes of forest and land fires in the Meranti Islands Regency, 2) the impact of forest and land fires on ecology, social and economy, 3) local wisdom owned by communities who are able to protect forests and land, 4) find prevention models forest and land fires based on integrated and effective institutions. This study uses a survey method. The data obtained were analyzed descriptively by using the mix methods approach by combining two forms of quantitative and qualitative approaches. Data analysis uses statistics with Pearson Correlation test and SWOT analysis. The results of the analysis concluded that the most dominant variables causing forest and land fires in the Meranti Islands Regency were socio-cultural conditions (69.06%) , this also has an impact on socio-cultural factors (62.68%). local wisdom in the community is one effort that can prevent forest and land fires, is the tradition of sago planting and bele kampung tradition. The results of the SWOT analysis produce an alternative S-O (Strenghts-Opportunity) strategy in cell 1 position with the power to take advantage of opportunities. The model for preventing forest and land fires based on integrated institutions is: 1) government, 2) research institutions are universities, 3) community institutions such as the Fire Concern Society (MPA).